Knowledge of ARV therapy in people living with HIV/AIDS (PLWHA) who have a dropping out history in Sumedang, Indonesia. An Overview - Imam Tri Sutrisno; Tuti Farida (Universitas Pendidikan Indonesia, 2022)
The prognosis of HIV infection improved following the discovery of ARV. Adherence to ARV therapy is an important factor in achieving the success of a therapeutic program. However, many PLWHA do not manage to achieve or maintain adequate levels of adherence to ARV therapy. This study aims to determine the knowledge of ARV therapy in People living with HIV/AIDS (PLWHA) who have a dropping out history. This is a descriptive study enrolled 70 samples by total sampling. The tool used to obtain data is a questionnaire that discusses the definition of ARV, the health service that provides ARV drugs, duration of treatment, treatment benefits, regularity in treatment, and impact if not consuming ARV. The data analysis used is descriptive analysis. 70 participants who had missed treatment, 53 people (75.7%), had good knowledge, and 17 people (24.3) had less knowledge. Most respondents knew about the definition of ARV, the health services that provide ARV drugs, the duration of treatment, regularity in treatment, the impact of not taking ARV, but did not know about the benefits of ARV therapy.